Wearables for running gait analysis: a systematic review - Mason, R.; Pearson, L. T.; Barry, G.; Young, F.; Lennon, O.; Godfrey, A.; Stuart, S. (Sports Medicine, 2023)
Background Running gait assessment has traditionally been performed using subjective observation or expensive laboratory-based objective technologies, such as three-dimensional motion capture or force plates. However, recent developments in wearable devices allow for continuous monitoring and analysis of running mechanics in any environment. Objective measurement of running gait is an important (clinical) tool for injury assessment and provides measures that can be used to enhance performance.